2019
DOI: 10.1177/1178641819840369
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol 12-Myristate 13-Acetate-Induced Changes in Chicken Enterocytes

Abstract: Increased intestinal epithelial permeability has been linked to many enteric diseases because it allows easy access of microbial pathogens and toxins into the system. In poultry production, the restrictions in the use of antibiotic growth promoters have increased the chances of birds being susceptible to different enteric diseases. Thus, understanding the mechanisms which compromise intestinal function is pertinent. Based on our previous observation which showed the primary chicken enterocytes in culture under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

6
1

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…In the current study, indomethacin appeared to only affect the outer epithelial cells of the enteroids without causing any lethality. Similarly, in a previous study using PMA where we observed significant cachectic effect of it on the enterocytes at concentrations of 1µg/ml or less [23,24], showed no significant effect on the enteroids. Monensin, an anticoccidial drug used in poultry production caused significant damage to the organoids and in some early studies it was reported to have toxic and necrotic effect on intestine [73].…”
Section: Discussionsupporting
confidence: 77%
“…In the current study, indomethacin appeared to only affect the outer epithelial cells of the enteroids without causing any lethality. Similarly, in a previous study using PMA where we observed significant cachectic effect of it on the enterocytes at concentrations of 1µg/ml or less [23,24], showed no significant effect on the enteroids. Monensin, an anticoccidial drug used in poultry production caused significant damage to the organoids and in some early studies it was reported to have toxic and necrotic effect on intestine [73].…”
Section: Discussionsupporting
confidence: 77%
“…In the current study, indomethacin appeared to affect the outer epithelial cells of the enteroids without causing any lethality. In a previous study using PMA, we observed significant cachectic effect of it on the enterocytes at concentrations of 1µg/ml or less [23,24], however, it showed no significant effect on the enteroids. Monensin, an anticoccidial drug used in poultry production caused significant damage to the organoids and some early studies it was reported to have toxic and necrotic effect on intestine [73].…”
Section: Discussionmentioning
confidence: 68%
“…The effect of some metabolic modulators, indomethacin, a prostaglandin inhibitor, PMA, a protein kinase C activator, and the monensin, an ionophore, anticoccidial antibiotic, on the enteroid morphologies were tested. Indomethacin produces ulcers in human and rat small intestines [72] however, it appeared only to shrink epithelial aspects of the enteroids whereas PMA showed no significant effect on the enteroids although our previous study with the effect of PMA on enterocytes showed significant cachectic changes in the enterocytes [23,24]. Monensin, on the other hand, damaged the organoids, however, it has been a preferred anticoccidial drug in the poultry and some early studies suggested its toxic and necrotic effect in the intestine [73].…”
Section: Discussionmentioning
confidence: 94%
“…Large scale screening assays may be possible if the organoids can be generated rapidly and cost-effectively. In the course of developing chicken enterocyte culture [23,24], we observed that the villus crypts of intestinal mucosa tend to self-repair to form spheroid-like structures resembling mini organoids that may have potential to study villus physiology. Hence, the objective of this study was to streamline the procedure, purify avian villus enteroids, characterize them, and study their potential as a screening tool using some selective chemicals and growth factors.…”
mentioning
confidence: 99%